Maximum number of repetitions and loss of velocity with cluster set configuration - Carballeira, E.; Iglesias-Soler, E.; Sánchez-Otero, T.; Castro-Gacio, X.; Mayo, X. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The purposes of this study were: monitoring the maximum number of repetitions (MNR) achieved before failure through a cluster set configuration (insertion of pause between every repetition), and studying the loss of velocity, of a high intensity parallel squat exercise (Sq). Methods: Nine male subjects (body mass=84.1±17.2 kg; height=175.6±8.41 cm; age=23.8±4.09 years) volunteered for participation in this study. All of them had at least 18 months of experience in weight training, with a minimum frequency of two training sessions per week. In a first session four repetition maximum load (4RM) for Sq was obtained. During a second session, called failure session (FS), subjects were instructed to perform MNR within each of the 3 sets of Sq with 4RM load. Three minutes rest were fixed between sets. Finally in a third session, called cluster session (CS), MNR was obtained with the same load than in FS, but individual resting time between each repetition was set as the ratio between the total pause in FS (360 seconds) and the sum of the total number of completed repetitions in FS minus 1. Results: The number of repetitions completed during FS was of 9.7±2.1. The obtained MNR in CS was of 45.3±32.2. The ratio MNR in CS respect the total number of completed repetitions in FS was 4.9±3.5. In addition, mean velocity of propulsive phase (Sanchez-Medina et al., 2010) resulted higher in CS than in FS (p=0.054, T-test for paired samples). Furthermore, repeated measures ANOVA showed that the loss of velocity in CS (% of first repetition velocity) was significant from 60 % of MNR. No significant correlation was found between MNR in CS and the total number of completed repetitions in FS. Discussion: The use of pauses between every repetition allows to improve mechanical performance of a training session (Haff et al., 2003; Iglesias-Soler et al., 2012). Since the development of sets to failure entails reduction in intensity of training (de Salles et al., 2009), the results of the present study suggest that CS is an interesting approach to improve mechanical stimuli of high intensity and high volume lower body workouts. These results are coincident with others obtained previously for upper-body exercises (Iglesias et al., 2010).